Random walks in random environment with Markov dependence on time - Boldrighini, C.; Minlos, R.A.; Pellegrinotti, A. (Condensed Matter Physics, 2008)
We consider a simple model of discrete-time random walk on Zν, ν = 1, 2, . . . in a random environment
independent in space and with Markov evolution in time. We focus on the application of methods based on
the properties of the transfer matrix and on spectral analysis. In section 2 we give a new simple proof of the
existence of invariant subspaces, with an explicit condition on the parameters. The remaining part is devoted
to a review of the results obtained so far for the quenched random walk and the environment from the point of
view of the random walk, with a brief discussion of the methods. Ми розглядаємо просту модель випадкового блукання з дискретним часом у Zν, ν = 1, 2, . . . у випадковому середовищi, що є незалежним у просторi i має маркiвську еволюцiю у часi. Ми зосереджуємось на застосуваннi методiв, що ґрунтуються на властивостях трансфер-матрицi i на спектральному аналiзi. У §2 ми подаємо просте доведення iснування iнварiантних пiдпросторiв, що використовує явну умову для параметрiв. Решта роботи присвячується огляду результатiв одержаних дотепер для замороженого випадкового блукання i оточення з точки зору випадкового блукання, а також короткому обговоренню методiв.